IPOT Syariah dan Layanan Investasi Saham dalam Perspektif Hukum Ekonomi Syariah - Armiyanti Sistira; Syafran Afriansyah; Hana Pertiwi; Syarif Ali Akbar; Lusiana Lusiana (Journal of Sharia and Legal Science, 2026)
This study aims to analyze the role of IPOT in providing stock investment services and examine its compliance with the principles of Sharia Economic Law. The study uses a normative legal method with a library research approach through analysis of literature, regulations, and concepts of Sharia Economic Law related to stock investment and the samsarah contract. The results show that IPOT plays a strategic role in the capital market ecosystem through the provision of online stock trading services, access to market information and investment research, portfolio management services, investment education, technology development, and collaboration with the financial industry. From a Sharia Economic Law perspective, IPOT's service mechanism has fulfilled the pillars and requirements of buying and selling, particularly regarding the ijab and qabul (contract) expressed through user agreement to the terms of service on the digital platform. Furthermore, IPOT's service practices are transparent, fair, and clear, thus aligning with Sharia principles. IPOT's role as a broker (simsar) is also considered to be in accordance with the samsarah contract because it has fulfilled the pillars and requirements stipulated in Sharia Economic Law.